1981
DOI: 10.1002/jcp.1041060104
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of mitotic cells from the surface of multicell spheroids during growth

Abstract: During the growth of EMT6/Ro mammary tumor multicell spheroids, a large number of cells are shed into the suspension medium. The rate of cell shedding was 218 cells per square millimeter of spheroid surface per hour, or up to 1.5% of the total spheroid cell content per hour. Shed cells had a clonogenic capacity equal to that of exponential monolayer cultures and were further characterized by volume distribution, mitotic index, flow cytofluorometry, and autoradiography. The results indicated that cells are rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…Cells which are shed from those spheroids investigated so far seem to be viable for the most part, and result from active biological processes not affected by the spinning rate, geometry, etc. of the culture conditions (Landry et al 1981). Since mitotic cells are most commonly found, this provides a method of obtaining synchronized cells from certain types of spheroids.…”
Section: Resultsmentioning
confidence: 99%
“…Cells which are shed from those spheroids investigated so far seem to be viable for the most part, and result from active biological processes not affected by the spinning rate, geometry, etc. of the culture conditions (Landry et al 1981). Since mitotic cells are most commonly found, this provides a method of obtaining synchronized cells from certain types of spheroids.…”
Section: Resultsmentioning
confidence: 99%
“…Mitotic inhibitors have been extracted from the necrotic core (see, for example, Levine et ai, 1984), and these prc-sumably diffuse through the spheroid affecting the mjtotic behaviour of some of the cells; however, this mechanism alone cannot be responsible for saturation since it requires that all the cells be inhibited if a continued increase in volume due to cell reproduction is to be prevented; this contradicts experimental observations. During mitosis, the reduced strength in binding between cells may cause individual cells to be shed into the surrounding matrix (Weiss, 1978;Landry et al, 1981) however, the cells that remain will still be reproducing so this mechanism cannot explain growth saturation either. In the models of Greenspan (1972) and subsequent similar studies, the crucial parameter for saturation arises in an expression stating that the contraction rate of the necrotic core is proportional to its volume; it is suggested that this is due to the process of disintegration of necrotic cellular material into simpler permeable compounds with a subsequent loss in volume.…”
Section: Discussionmentioning
confidence: 99%
“…Equation (7) neglects the effects of the mitotic cell loss due to shedding on spheroid growth, which is valid if the spheroid diameter is small (Landry et al, 1981). Equation (7) can also be rewritten in term of the spheroid radius r…”
Section: Mts Growthmentioning
confidence: 99%